Enhanced Nitrate and Phosphate Removal in a Denitrifying Bioreactor with Biochar. Issue 2 (1st March 2015) - Bock, Emily; Smith, Nick; Rogers, Mark; Coleman, Brady; Reiter, Mark; Benham, Brian; Easton, Zachary M.
Abstract : Denitrifying bioreactors (DNBRs) are an emerging technology used to remove nitrate‐nitrogen (NO3 − ) from enriched waters by supporting denitrifying microorganisms with organic carbon in an anaerobic environment. Field‐scale investigations have established successful removal of NO3 − from agricultural drainage, but the potential for DNBRs to remediate excess phosphorus (P) exported from agricultural systems has not been addressed. We hypothesized that biochar addition to traditional woodchip DNBRs would enhance NO3 − and P removal and reduce nitrous oxide (N2 O) emissions based on previous research demonstrating reduced leaching of NO3 − and P and lower greenhouse gas production associated with biochar amendment of agricultural soils. Nine laboratory‐scale DNBRs, a woodchip control, and eight different woodchip‐biochar treatments were used to test the effect of biochar on nutrient removal. The biochar treatments constituted a full factorial design of three factors (biochar source material [feedstock], particle size, and application rate), each with two levels. Statistical analysis by repeated measures ANOVA showed a significant effect of biochar, time, and their interaction on NO3 − and dissolved P removal. Average P removal of 65% was observed in the biochar treatments by 18 h, after which the concentrations remained stable, compared with an 8% increase in the control after 72 h. Biochar addition resulted in average NO3 − removal of 86% after 18 h and 97% after 72 h, compared with only 13% at 18 h and 75% at 72 h in the control. Biochar addition also resulted in significantly lower N2 O production. These results suggest that biochar can reduce the design residence time by enhancing nutrient removal rates.